Konseling KB Menggunakan Flashcard terhadap Peningkatan Pengetahuan, Sikap dan Keikutsertaan Kontrasepsi IUD dan MOW Pascasalin - Vera Suzana Dewi Haris (Jurnal Kesehatan, 2017)
Flash card is an effective tool in Family planning counseling because it is easy to bring to the room when carrying out the IUD and MOW contraceptives counseling for postnatal mother program. This study aimed to measure the difference in knowledge and attitudes of a postnatal mother about IUD and MOW contraceptives before and after provision information program of family planning by flash card and measure the correlation in the increase of knowledge and attitude after provision family planning counseling by a flash card with the postnatal IUD and MOW contraceptives participation.This study uses a quasi-experimental research design with one group pretest-posttest design. There were 52 total samples fulfilling the inclusion criteria. The analysis was Wilcoxon, chi-square and point biserial test. The results showed that there was difference in knowledge and attitudes about family planning before and after IUD and MOW postnatal family planning counseling by flash card (p-value=0,000), there was  a positive correlation between the knowledge and attitudes of postnatal mother about family planning after counseling by flash card with the postnatal IUD and MOW contraceptives participation (p value =0,001 and 0,000), and there was  a positive correlation between the increase of knowledge and attitude with the postnatal IUD and MOW contraceptives participation by p value=0,002 and 0,001 by mean of weak and adequate relationship degree. The conclusions of this research are knowledge and attitude of a postnatal mother about family planning after the provision of family planning counseling by flash card is better than before the provision of family planning counseling.